2019
DOI: 10.1093/jxb/erz328
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific respiratory burst oxidase homolog-dependent H2O2 signaling to the plasma membrane H+-ATPase confers potassium uptake and salinity tolerance in Cucurbitaceae

Abstract: Potassium (K+) is a critical determinant of salinity tolerance, and H2O2 has been recognized as an important signaling molecule that mediates many physiological responses. However, the details of how H2O2 signaling regulates K+ uptake in the root under salt stress remain elusive. In this study, salt-sensitive cucumber and salt-tolerant pumpkin which belong to the same family, Cucurbitaceae, were used to answer the above question. We show that higher salt tolerance in pumpkin was related to its superior ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 74 publications
(103 reference statements)
6
46
0
Order By: Relevance
“…Knocking out of RBOHD in pumpkin via genome editing led to a saltsensitive phenotype: lower root apex H 2 O 2 and K + content and GRF12, AHA1 and HAK5 expression. Therefore, salt tolerance in pumpkin is regulated by RBOHD-dependent transcriptional and post-translational activation of AHAs operating upstream of HAK5 (Huang et al, 2019). In this study, H 2 O 2 content increased significantly in plants silencing HvAKT2 and HvHAK1, but significantly reduced in overexpression plants under drought stress, which were also linked to altered K + and H + homoeostasis and drought tolerance in barley (Figures 4-8).…”
Section: Hvakt2 and Hvhak1 Modulate Ion Homoeostasis And Signalling Fmentioning
confidence: 49%
See 1 more Smart Citation
“…Knocking out of RBOHD in pumpkin via genome editing led to a saltsensitive phenotype: lower root apex H 2 O 2 and K + content and GRF12, AHA1 and HAK5 expression. Therefore, salt tolerance in pumpkin is regulated by RBOHD-dependent transcriptional and post-translational activation of AHAs operating upstream of HAK5 (Huang et al, 2019). In this study, H 2 O 2 content increased significantly in plants silencing HvAKT2 and HvHAK1, but significantly reduced in overexpression plants under drought stress, which were also linked to altered K + and H + homoeostasis and drought tolerance in barley (Figures 4-8).…”
Section: Hvakt2 and Hvhak1 Modulate Ion Homoeostasis And Signalling Fmentioning
confidence: 49%
“…H 2 O 2 is an early response of K + deficiency and externally added H 2 O 2 was sufficient for the induction of the high-affinity K + uptake (Shin and Schachtman, 2004;Wang et al, 2017). Although there was no report on the correlation between AKT2 and HAK1 regulated K + homoeostasis and H 2 O 2 accumulation in plant drought tolerance, positive relationships between H 2 O 2 production and K + accumulation under salt stress were found for Arabidopsis, cucumber (Cucumis sativus) and pumpkin (Cucurbita moschata) (Huang et al, 2019;Ma et al, 2012;Redwan et al, 2016). For instance, it was demonstrated that higher salt tolerance in pumpkin is related to its higher K + uptake and H 2 O 2 accumulation in the root apex.…”
Section: Hvakt2 and Hvhak1 Modulate Ion Homoeostasis And Signalling Fmentioning
confidence: 99%
“…Rapid induction of plasma membrane and vacuolar proton pumps to maintain negative membrane potential and to facilitate Na + /H + pumps was reported in salt-tolerant genotypes under stress (Vera-Estrella et al, 2005;Shabala and Mackay, 2011). Both Na + exclusion and K + uptake from rhizospheric region and selective upward transport mediated by xylem unloading is energy dependent and supported by increased action of ATPases and pyrophosphatases (Chakraborty et al, 2018;Niu et al, 2018a;Huang et al, 2019). To date, there are 11 variants of AHA (a plasma membrane ATPase) reported in rice (Ueno et al, 2005).…”
Section: Differential Induction Of H + Pumps Suggests Relative Importmentioning
confidence: 99%
“…Most reports indicate that exogenous NO supplementation has a role in the protection of plants by alleviating heavy metal stress, including Cd [50], Cu [51], Pb [52], and so forth. There are a few reports showing that the application of exogenous NO in combination with heavy metals enhances metal toxicity [53]. The contribution of endogenous NO to plant metal stress was also reported to exert both cytotoxic and cytoprotective effects [14].…”
Section: Discussionmentioning
confidence: 99%
“…NMT has been reported to be an effective approach to studying ion uptake and accumulation in plants and animals. The fluxes of ions, such as Cd 2+ , Ca 2+ , K + , Pb 2+ , and so forth, can be measured by NMT under normal physiological conditions [31,53,54]. Heavy metal transport is crucial for understanding metal uptake mechanisms in plants.…”
Section: Discussionmentioning
confidence: 99%